Registration of 'Purl' soft white winter wheat. Issue 3 (24th September 2020) - Carter, A. H.; Balow, K. A.; Shelton, G. B.; Burke, A. B.; Hagemeyer, K. E.; Worapong, J.; Higginbotham, R. W.; Chen, X. M.; Engle, D. A.; Murray, T. D.; Morris, C. F.
Abstract: There are numerous traits that soft white winter (SWW) wheat ( Triticum aestivum L.) cultivars require to be successful in the U.S. Pacific Northwest. High yield potential, high grain volume weight, acceptable end‐use quality, winter hardiness, resistance to Cephalosporium stripe, and high falling number are just a few of the desired traits. Although many of these traits are driving factors toward releasing a new cultivar, two traits are essential if a cultivar is to be successful in the Pacific Northwest: stripe rust resistance and strawbreaker foot rot (eyespot) resistance. The objective of this research was to develop a SWW cultivar with improved resistance to current stripe rust races, that carries genes for strawbreaker foot rot resistance, is winter hardy, and has high yield potential in the intermediate (400–500 mm) and high (>500 mm) rainfall regions of eastern Washington. 'Purl' (Reg. no. CV‐1166, PI 691558) SWW wheat was developed and released in March 2018 by the Agricultural Research Center of Washington State University. Purl was tested under the experimental designations MAS08019‐92‐1‐S‐s and WA8234, which were assigned through progressive generations of advancement. Purl is a semi‐dwarf cultivar adapted to intermediate‐ to high‐rainfall wheat production regions of Washington. Purl has high‐temperature adult‐plant resistance to stripe rust, carries the Pch1 gene for strawbreaker foot rot, is intermediate in height, has midseason maturity, and has high test weight and grain yield potential. Purl has end‐use quality properties similar to those of 'Stephens', 'Puma', and 'Madsen' and is suitable for cookie, cake, and cracker production.